Mechanical power is associated with cardiac output and pulmonary blood flow in an experimental acute respiratory distress syndrome in pigs - Zhang, Yingying; Wittenstein, Jakob; Braune, Anja; Theilen, Raphael; Maiello, Lorenzo; Benzi, Giulia; Bluth, Thomas; Kiss, Thomas; Ran, Xi; Koch, Thea; Rocco, Patricia R. M.; Schultz, Marcus J.; et al. (Frontiers in Physiology, 2024)
Background Despite being essential in patients with acute respiratory distress syndrome (ARDS), mechanical ventilation (MV) may cause lung injury and hemodynamic instability. Mechanical power (MP) may describe the net injurious effects of MV, but whether it reflects the hemodynamic effects of MV is currently unclear. We hypothesized that MP is also associated with cardiac output (CO) and pulmonary blood flow (PBF). Methods 24 anesthetized pigs with experimental acute lung injury were ventilated for 18 h according to one of three strategies: 1) Open lung approach (OLA), 2) ARDS Network high-PEEP/FIO2 strategy (HighPEEP), or 3) low-PEEP/FIO2 strategy (LowPEEP). Total MP was assessed as the sum of energy dissipated to overcome airway resistance and energy temporarily stored in the elastic lung tissue per minute. The distribution of pulmonary perfusion was determined by positron emission tomography. Regional PBF and MP, assessed in three iso-gravitational regions of interest (ROI) with equal lung mass (ventral, middle, and dorsal ROI), were compared between groups. Results MP was higher in the LowPEEP than in the OLA group, while CO did not differ between groups. After 18 h, regional PBF did not differ between groups. During LowPEEP, regional MP was higher in the ventral ROI compared to OLA and HighPEEP groups (2.5 ± 0.3 vs. 1.4 ± 0.4 and 1.6 ± 0.3 J/min, respectively, P < 0.001 each), and higher in the middle ROI compared to the OLA group (2.5 ± 0.4 vs. 1.6 ± 0.5 J/min, P = 0.04). MP in the dorsal ROI did not differ between groups (1.4 ± 0.9 vs. 1.4 ± 0.5 vs. 1.3 ± 0.8 J/min, P = 0.916). Total MP was independently associated with CO [0.34 (0.09, 0.59), P = 0.020]. Regional MP was positively associated with PBF irrespective of the regions [0.52 (0.14, 0.76), P = 0.01; 0.49 (0.10, 0.74), P = 0.016; 0.64 (0.32, 0.83), P = 0.001 for ventral, middle, and dorsal ROI, respectively]. Subgroup analysis revealed a significant association of MP and CO only in the OLA group as well as a significant association between MP with regional PBF only in the HighPEEP group. Conclusion In this model of acute lung injury in pigs ventilated with either open lung approach, high, or low PEEP tables recommended by the ARDS network, MP correlated positively with CO and regional PBF, whereby these clinically relevant lung-protective ventilation strategies influenced the associations.